Time frequency analysis on financial data - Cheng, Chi. (2011)
The joint time-frequency analysis is a signal processing technique in which signals are represented in both time domains and frequency domains simultaneously. Nowadays, this analysis technique has become a popular and powerful tool for analyzing non-stationary time series. One basic difficult in financial time series analysis is to deal with the non-stationary property, as financial time series contain stochastic components that are time dependent. Traditional methods of business cycle analysis like correlation analysis, spectral analysis cannot take the time-varying characteristics of the business cycle into consideration. So in this report, we introduced a new technique into the financial time series analysis: the Short Time Fourier Transform based analysis that has been implemented extensively in the area of digital signal processing. And it's been found that time frequency analysis methods have great potential of revealing new phenomena and changing the way we view and think about financial time series.